Inflammation and sarcopenia: A focus on circulating inflammatory cytokines - Pan, Linyuan; Xie, Wenqing; Fu, Xin; Lu, Wenhao; Jin, Hongfu; Lai, Jieyu; Zhang, Aohan; Yu, Yongle; Li, Yusheng; Xiao, Wenfeng (Experimental gerontology, 2021)
Sarcopenia is an aged-related syndrome that is progressive and can be accelerated by other concomitant disease states. Sarcopenia, characterized by loss of skeletal muscle mass, reduced muscle strength, and/or reduced physical performance, is one of the main reasons for limitation of daily activities in the elderly. It is associated with an increased incidence of many adverse events, such as dysfunction, falls, weakness, hospitalization, disability and even death. Sarcopenia justifies one of the most widely accepted theories that low-grade chronic inflammation associated with aging, known as inflammatory aging, is important to the pathogenesis of many age-related diseases. Currently, the diagnosis of sarcopenia is based on a comprehensive assessment of three aspects: muscle mass, muscle strength and physical performance. The measurement of muscle mass is complicated, as the measurement of muscle strength and gait speed is easily affected by the physical conditions of the subjects. This makes the measurements inaccurate and prospective, and it is difficult to achieve continuous, purposeful monitoring. In addition, serum levels of inflammatory cytokines change as inflammatory states develop in the elderly population. This manuscript focuses on the correlation between serum inflammatory cytokines and sarcopenia in recent years, plus the possible underlying mechanisms. •Low-grade chronic inflammation plays a leading role in the onset and development of sarcopenia.•The combination of diverse circulating inflammatory cytokines may improve the sensitivity and specificity of sarcopenia diagnosis.•Whether high levels of inflammatory cytokines can be used as a basis for the diagnosis of sarcopenia patient needs in-depth research studies.